Death by bubble tea - Chow, Jennifer J. (Chow, Jennifer J. L.A. night market mysteries, 2022)
When two cousins open a food stall at a Los Angeles night market, a customer dies after drinking their bubble tea, and they set out to find the killer and clear their names.